Training Models for Nurses to Improve Patient Safety Compliance: A Literature Review - Ceril Pungus; Lisa Musharyanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nurses spend most of their period with sufferers during clinical care, which allows them to promote intercommunication with patients. In developing close relationships with patients, team training is needed that can improve patient safety for nurses. The purpose of the literature review is to find out the types or models of training that improve Patient Safety and to determine the level of nurse compliance in the implementation of Patient Safety. The method consists of identifying questions and identifying relevant articles using the ScienceDirect, PubMed, and Scopus databases with keywords. Selection of articles using PRISMA Flowchart, The Joana Briggs Institute (JBI), charting data and compiling, summarizing, and reporting the results. The results of 168 articles are relevant. to the title and abstract, that are obtained.6 articles that met the inclusion and exclusion criteria. Three types or models of training provided by nurses were found to improve patient safety, namely patients as part of a team, team training programs, and simulation-based team training. The article also found the level of nurse compliance in the implementation of patient safety. Professional team training will have a positive impact on clinical practice routines and will also demonstrate the importance of patient safety. Hospital health services need to carry out prevention of errors learning fully practicable and establishing individual safety in health care curricula about existent health care necessary to assure the continuity of progress in quality healthcare. Abstrak: Perawat menghabiskan sebagian besar waktu dengan pasien selama perawatan klinis, yang memungkinkan mereka untuk mengembangkan hubungan dekat dengan pasien. Dalam mengembangkan hubungan yang dekat dengan pasien diperlukan pelatihan tim yang dapat meningkatkan patient safety pada perawat. Tujuan literature review untuk mengetahui jenis-jenis atau model-model pelatihan yang meningkatkan Patient Safety dan untuk mengetahui tingkat kepatuhan perawat pada pelaksanaan Patient Safety. Metode terdiri dari identifikasi pertanyaan, identifikasi artikel relevan menggunakan database ScienceDirect, PubMed,  dan Scopus dengan keyword. Seleksi artikel menggunakan PRISMA Flowchart, The Joana Briggs Institute (JBI), data charting dan menyusun, meringkas serta melaporkan hasil. Hasil dari 168 artikel terkait judul dan abstrak, diperoleh 6 makalah yang memenuhi standar inklusi dan eksklusi. Ditemukan tiga jenis atau model pelatihan yang diberikan oleh perawat untuk meningkatkan patient safety yaitu pasien sebagai bagian dari tim, program pelatihan tim, dan pelatihan tim berbasis simulasi. Dari artikel juga ditemukan tingkat kepatuhan perawat pada pelaksanaan patient safety. Pelatihan tim terprofessional akan berdampak positif pada rutinitas praktik klinis sehingga juga akan menunjukkan pentingnya keselamatan pasien. Layanan kesehatan rumah sakit perlu melakukan pendidikan keselamatan pasien sebanyak mungkin dan membentuk kurikulum keselamatan pasien individual berdasarkan kebutuhan aktual perawatan kesehatan untuk memastikan kemajuan berkelanjutan di layanan kesehatan yang berkualitas.